1997
DOI: 10.3758/bf03214348
|View full text |Cite
|
Sign up to set email alerts
|

Memory-basedsame-different conceptualization by pigeons

Abstract: Wefirst trained pigeons to peck one button (same) after the successive presentation of 16identi-cal pictures and to peck a second button (different) after the successive presentation of 16 nonidentical pictures. Later, we tested the birds with other lists of same and different items composed of completely novel pictures. Accuracy to the testing lists reliably exceeded chance levels, thus demonstrating same-different conceptualization by pigeons under conditions that, for the first time, (1) eliminated purely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…at least when pecked at directly by the birds (Carter and Werner, 1978;Wright, 1997;Young et al, 1997Young et al, , 1999. The central location of the objects may have been more problematic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…at least when pecked at directly by the birds (Carter and Werner, 1978;Wright, 1997;Young et al, 1997Young et al, , 1999. The central location of the objects may have been more problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Over the four experiments, the pigeons had little problem with displays in which moderate to large changes occurred between successive items, but Experiments 1 and 2, showed that small, centrally located changes were difficult for the birds. Young et al (1997Young et al ( , 1999 found that pigeons could successfully discriminate very small successively presented icon stimuli, but in their case a large number of items were presented in each sequence and each item was pecked. In humans, detecting certain kinds of changes or difference between successively presented pictures seems to require focused attention to be specifically brought to the area of the display that is changing (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy to the training stimuli averaged from 83% to 93% correct and accuracy to the testing stimuli averaged from 71% to 79% correct; in each case, choice accuracy reliably exceeded the chance score of 50% correct. Such robust discrimination learning and stimulus generalization attest to the pigeon's acquisition of an abstract same-different concept (for more on the nature of this concept, see Wasserman, Young, & Nolan, 2000;Young, Wasserman, & Dalrymple, 1997;. Should these results be taken at face value?…”
Section: Same/different Learning Using Multiple-item Displays: Effectmentioning
confidence: 99%
“…items (Young, Wasserman, & Dalrymple, 1997;Young et al, 1999). Entropy is a precise mathematical measure of categorical variability that was proposed by Shannon and Weaver (1949): ( 1) where H(A) is the entropy of categorical variable A, a is a category of A, and p a is the proportion of observed values within that category.…”
mentioning
confidence: 99%